Modelo de estratégias de gestão para utilização em indicação geográfica de rendas e bordados - Bianchini, Ilka Maria Escaliante (2019)
With the globalized economy, various organizations are seeking to innovate to survive. One tool that provides differentials for products of small or large organizations is the Geographical Indications - IG, which in Brazil were instituted by Law No. 9,279, of May 14, 1996, known as the Industrial Property Law, which regulates rights and obligations. relating to industrial property and established two types of GI, the Geographical Indication of Origin - IP and the Denomination of Origin - DO. Within Industrial Property, Geographical Indications value and protect traditional products linked to a locality, while making positive contributions to the local economy. Registration of an IG is the responsibility of the National Institute of Industrial Property - INPI, governed by resolution no. 75 of the Institute, which establishes the conditions for such registration. The lace and embroidery handicraft production associations in Brazil, which have obtained the seal of geographical indication, aggregate artisans who derive a living from their families almost exclusively by selling the products of the associations. Several actions and management tools can be associated with GI and used by organizations, aiming at better performance in the market. Management Model is a set of actions that aim to achieve goals. Strategic management alignment can be understood as the organization of the company's internal structures as its procedural systems, to facilitate the achievement of the organization's objectives. This study aimed to characterize the profile of the Irish Lace, Renaissance and Embroidery Filé associates and associations, sought to relate their level of strategic alignment with their markets, aiming to develop a theoretical management model and strategies that promote adequacy and integration. between market and administrative structure of associations. The work started with bibliographic research, which preceded the field research. In the bibliographic research were used articles, theses and dissertations available in the online bases of the periods of the Coordination of Improvement of Higher Education Personnel - CAPES. The field research was carried out in Brazil, from May to June 2019, and in Portugal, from November 2018 to April 2019. Data were collected through a semi-structured questionnaire. The research had an intentional non-probabilistic sampling and used the methodology called snowball. It was found that not all associations can work within the premises and requirements of the Geographical Indication seal - IG. INBORDAL's strategic alignment is currently effective in maintaining the economic aspects of the community. ASDEREN is at an intermediate stage in the search for the best strategic alignment and has been promoting important actions to reach an economic balance for the association. CONARRENDA still faces more severe structural and cultural problems in its quest for efficiency in strategic alignment.